The Relationship of Learning Quality to the Learning Motivation of Undergraduate Health Administration Students in the Online Learning Period - Ria Efkelin; Enni Juliani; Ellynia Ellynia; Sarah Geltri Harahap (GLOBAL HEALTH SCIENCE GROUP, 2022)
Learning is the interaction of students with education and learning resources in a learning environment. Based on the researcher's experience while serving as a lecturer, it was known that the objectives to be achieved from learning were still relatively low. Indicators of the problems that occurred included complaints from lecturers about the lack of responsiveness of learning in participating in lecture activities, namely the final grades obtained by students for several courses were not evenly distributed. In teaching and learning activities, motivation could be said as the overall driving force in a person that causes learning activities and ensures the continuity of learning activities, and provides direction to learning activities so that the goals desired by the learning subjects can be achieved. The research design in this study was a research design with a quantitative descriptive approach. The population in this research were all health students at STIKes RS Husada, and two other higher education institutions, the samples used were students of level 1, II, and III Health Administration. in STIKes RS Husada, STIKes Pamenang Pare Kediri, STIKes Brebes, the time in this study was from April to December 2022. The univariate was concluded that from 131 respondents, it was found that the quality of learning at most was good with a total of 89 (67.9%), based on the student motivation variable, the results were 126 (96.2%), while the results of the bivariate analysis were based on the Chi-Square table. Tests showed that there is a strong and positive relationship between the quality of learning and student motivation to learn with a sig value of 0.000, which is <0.05.